If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -9) = (x + -3) Reorder the terms: 3(-9 + x) = (x + -3) (-9 * 3 + x * 3) = (x + -3) (-27 + 3x) = (x + -3) Reorder the terms: -27 + 3x = (-3 + x) Remove parenthesis around (-3 + x) -27 + 3x = -3 + x Solving -27 + 3x = -3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -27 + 3x + -1x = -3 + x + -1x Combine like terms: 3x + -1x = 2x -27 + 2x = -3 + x + -1x Combine like terms: x + -1x = 0 -27 + 2x = -3 + 0 -27 + 2x = -3 Add '27' to each side of the equation. -27 + 27 + 2x = -3 + 27 Combine like terms: -27 + 27 = 0 0 + 2x = -3 + 27 2x = -3 + 27 Combine like terms: -3 + 27 = 24 2x = 24 Divide each side by '2'. x = 12 Simplifying x = 12
| 4(c-3)+4=2+c-10 | | W^2+2w-240=0 | | 0.005(1-k)+0.03(k-7)=1 | | 7x-2=3x-14 | | 15x-9=18x-2 | | 2y=3/2x-12 | | (2x+y^2)(2y+4x-3y^2)= | | 3xy*dx+(x^2+y^2)*dy=0 | | 1/5x-1/6(x-3)=6x | | 186=(5y)(4y+3) | | -5(6-x)+6=4-7(x-2) | | ay^2+7y-8ay=56 | | 7/4=5/b | | xy*dx-(2x+4y)*dy=0 | | 2*2+y=-5 | | 2*1+y=-5 | | -3x=17+3y-z | | 2*0+y=-5 | | (4x-9)(64x^2-9)=0 | | y^2*dy=x(xdy-ydx)e^x/y | | m^3+2m^2-63m=0 | | 2(2x^2+y^2)*dx-xy*dy=0 | | [x^2+7x-71]=27 | | (2y-5)(3y+7)=0 | | 144=x+38 | | 3x-5(x-3)=-7+2x-10 | | 4*2+y=8 | | p-3u=3k | | 4*1+y=8 | | -3k=3u+-p | | 2(b-24)=44-4(b-4) | | x(x-3)(x+8)=0 |